THE AUTOMATION OF ACCOUNTING SYSTEMS: TRANSFORMING FINANCIAL MANAGEMENT (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The automation of accounting systems has become a pivotal transformation in financial management across various industries. This study examines the impact of accounting automation on efficiency, accuracy, and cost reduction. Through a comprehensive survey of organizations that have implemented automated accounting systems, we analyze the perceived benefits and challenges of such technologies. The results indicate a significant increase in operational efficiency and accuracy, with a corresponding reduction in labor costs. The findings suggest that while initial investment and integration pose challenges, the long-term advantages of automation justify the transition. This paper provides a detailed analysis of the effects of accounting system automation, offering insights for businesses considering this technological shift.